The Sun A User's Manual - Vita-Finzi, Claudio (Springer Netherlands : Imprint: Springer, 2008)
The Sun is an account of the many ways in which our nearest star affects our planet, how its influence has changed over the last few centuries and millennia, and the extent to which we can predict its future impact. The Sun's rays foster the formation of Vitamin D by our bodies, but it can also promote skin cancer, cataracts, and mutations in our DNA. Besides providing the warmth and light essential to most animal and plant life, solar energy contributes substantially to global warming. Although the charged particles of the solar wind shield us from harmful cosmic rays, solar storms may damage artificial satellites and cripple communication systems and computer networks. The Sun is the ideal renewable energy source, but its exploitation is still bedevilled by the problems of storage and distribution. Our nearest star, in short, is a complex machine which needs to be treated with caution, and this book will equip every reader with the knowledge that is required to understand the benefits and dangers it can bring.